Introduction to space sciences and spacecraft applications - Campbell, Bruce A., 1955-
Introduction to Space Sciences and Spacecraft Applications explains the fundamentals of design, application, and operation of space-based systems. It focuses on the most common uses of spacecraft today: communications, remote sensing, and navigation. You will learn about the basic systems required by most spacecraft and the methodology used to design a spacecraft. The complexities of orbital mechanics are also fully explained. Amply illustrated with diagrams and photographs, each chapter contains exercises, historical information, and additional reference materials. Written primarily for undergraduate space engineering students, this is an excellent source for the space professional and a fascinating book for the general reader.